(untitled) (Bangladesh Journal of Microbiology, 2019)
Antimicrobial resistance is a mounting threat to the control of infectious diseases worldwide. Due to the increasing rate of drug resistance, there is continuous requirement for new and safe antimicrobial agents both for therapeutic purposes and food industries. The potential of bacteriocin has attracted much attention in recent years.We characterized bacteriocin like substances produced by Lactobacillus casei. This bacterium produces bacteriocin like substances that have the ability to inhibit multi-drug resistant pathogenic bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, and Proteus vulgaris. To investigate the antimicrobial property of the bacteriocin like substances produced by L.casei, cell free supernatant (CFS) was prepared and antagonistic activity of cell free supernatant was determined by agar well diffusion method. Production of bacteriocin like substances was greatly affected by nutrient media, pH, temperature and incubation period. Highest inhibitory activity was observed when L.casei was grown in MRS broth (De Man, Rogosa and Sharpe broth) (pH 4.0) for 72 hoursat 37°C. The active components of CFS responsible for antagonistic activity are proteinaceous in nature since they are susceptible to heat treatment. Partial purification of this CFS was done by organic solvent extraction method. Among the eight isolates tested, only S. auereus, Proteus vulgaris and K. pneumoniae showed more sensitivity to the partially purified crude bacteriocin like substances (CBLS) than CFS. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 01-06